Evaluation of graft osteogenesis using fractal dimension analysis on cone-beam computed tomography images following maxillary sinus lift surgery - Emre Sozen; Emre Aytugar; Elif Tarim Ertas; Erhan Cene; Muhammed Isa Kara (BMC Oral Health)
Abstract Background Fractal dimension (FD) analysis is a method used to numerically characterize the complexity of structures or tissues. After sinus lift procedures, the graft material gradually transforms into natural bone over time. This study aimed to evaluate the interpretability of this transformation by assessing changes in FD values. Methods In this retrospective study, data from a total of 36 patients (42 hemimaxillae), including 13 females (17 hemimaxillae) and 23 males (25 hemimaxillae), were analyzed. Cone-beam computed tomography (CBCT) images obtained preoperatively and at six months postoperatively from patients who underwent sinus lift surgery with graft placement in the maxillary molar region were included in the evaluation. The pre- and postoperative images were superimposed using anatomical reference points. Examination areas were determined on cross-sectional slices from the grafted and adjacent non-grafted bone areas (used as control) within the maxillary molar region. FD analysis was performed on these areas. FD values from the grafted and control bone regions at baseline and six months were recorded. Paired and independent sample t-tests were used for statistical analysis, with statistical significance set at p < 0.05. Results FD values derived from CBCT images showed a statistically significant difference between the initial state of the graft immediately after placement (G0) and its state six months postoperatively (G1) (p < 0.05). The mean FD values were 1.297 for G0 and 1.279 for G1. However, no significant difference was observed between the initial state (B0) and the six-month follow-up state (B1) of the trabecular bone in the posterior region used as a control (p > 0.05). The FD values in the G0 group showed minimal variation across gender and age groups, consistently ranging between 1.295 and 1.299. No significant differences in FD values were identified based on gender or age groups (p > 0.05). Conclusions The findings of this study suggest that FD analysis may serve as a useful adjunctive tool for evaluating graft osteogenesis.